2016
DOI: 10.4196/kjpp.2016.20.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate rescues LPS-impaired adult hippocampal neurogenesis through suppressing the TLR4-NF-κB signaling pathway in mice

Abstract: Adult hippocampal dentate granule neurons are generated from neural stem cells (NSCs) in the mammalian brain, and the fate specification of adult NSCs is precisely controlled by the local niches and environment, such as the subventricular zone (SVZ), dentate gyrus (DG), and Toll-like receptors (TLRs). Epigallocatechin-3-gallate (EGCG) is the main polyphenolic flavonoid in green tea that has neuroprotective activities, but there is no clear understanding of the role of EGCG in adult neurogenesis in the DG after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 57 publications
3
49
0
Order By: Relevance
“…We observed that the production of NO and iNOS in LPS-induced murine macrophages was reduced by OCB treatment. During inflammation, macrophages have three major functions: antigen presentation [14], phagocytosis [15], and immunomodulation [15,16], which is mediated through the production of various cytokines and growth factors. The inflammatory process is usually tightly regulated, involving both signals that initiate and maintain inflammation and signals that resolve inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the production of NO and iNOS in LPS-induced murine macrophages was reduced by OCB treatment. During inflammation, macrophages have three major functions: antigen presentation [14], phagocytosis [15], and immunomodulation [15,16], which is mediated through the production of various cytokines and growth factors. The inflammatory process is usually tightly regulated, involving both signals that initiate and maintain inflammation and signals that resolve inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Nakanishi and co‐workers showed that catechins can inhibit VEGF production and COX‐2 expression in HDPCs. Catechins have also been reported to have potential effects on suppressing inflammation mediated by the NF‐κB pathway (Ravindranath & Ravindranath, ), especially in lipopolysaccharide‐mediated cerebral injury (Seong et al, ). Hirao and colleagues reported that catechins can reduce inflammatory reactions via MAPK pathways in dental pulp cells and that up‐regulated expression of IL‐8 or prostaglandin‐E2 in streptococci could be inhibited by catechins (Hirao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…RES was shown to attenuate LPS and Aβ-mediated microglia neuroinflammation, inhibiting the TLR-4/NF-κB/STAT pathway [180]. EGCG was able to abrogate LPS-impaired adult hippocampal neurogenesis, silencing the TLR-4 signaling in mice [181][182][183].…”
Section: Neurodegenerationmentioning
confidence: 97%